Melancholic features and dream masochism in patients with major depression - Ağargün, Mehmet Yücel; Cartwright, Rosalind (Küre İletişim Grubu A.Ş., 2016)
To investigate whether untreated depressed subjects with melancholic features have higher dream masochism scores than those without melancholic features, the dreams of a group of community volunteers undergoing divorce were recorded in the sleep laboratory. A second question of interest was whether there was a gender difference in dream masochism. We also examined whether melancholic depressed individuals tend to report masochistic dreams closer to morning. Three groups of depressed with and without melancholic features and a non-depressed group had three laboratory nights of sleep. On the third night, dream reports were elicited from each period of rapid eye movement (REM) sleep. Dream masochism, as defined by Beck (1967), was scored as present if the dreams had any one of ten characteristics. Subjects with melancholic features had higher dream masochism scores than those who did not meet depression criteria. Presence of melancholic features did not affect gender difference in dream masochism. Melancholic depressed individuals had higher DM scores in the second half than the first half night, whereas nonmelancholic depressed individuals and non-depressed subjects did not differ between the halves of the night. These findings suggest that melancholic depressed individuals express deeper levels of self-criticism and self-blaming in their dreams. REM sleep deprivation closer to morning by dream collection method may improve diurnal mood symptoms and negative dream content in major depression.
Keywords: Depression; Diurnal Rhythm; Dream Masochism; Dreams; Melancholic Features; REM sleep